Taking Calculated Risks: The Story of the Cannibal Mothers (2 Kings 6:24–7:20) - Matthews, Victor H. 1950- (2013)
Embedded in the collection of tales about the prophet Elisha is a series of three inter-connected scenes reflecting the depredations of siege warfare and the breakdown of normal social control mechanisms (2 Kgs 6:24–7:20). Each scene plays upon the tendency by humans whenever possible to calculate the risks that they face. Presented in these three episodes is a simple proposition: given current conditions, what actions are worth the risk? To make this clear the storyteller shapes the drama in order to highlight the choices that are made by the unnamed king and two widows as they attempt to deal with an emergency situation. The choices made by these characters include whether to take a risk and handle the crisis in their own way or to be risk-averse and rely upon the covenantal injunction to trust Yahweh to provide what is needed.
Keywords: Type-scene; Covenant; Cannibalism; risk calculation; Siege warfare